(untitled) ("Conference on Universal Science Research 2023", 2026)
In the modern education system, teaching that takes into account students’ individual psychological characteristics, interests, and intellectual strengths is becoming increasingly important. Traditional education often relies on a “one-size-fits-all” approach, offering the same materials and methods to all students, which prevents many learners from fully realizing their potential. Howard Gardner’s Theory of Multiple Intelligences (1983) proposes that intelligence should not be limited to a single IQ indicator but divided into several independent types. Gardner initially identified seven types of intelligence (linguistic, logical-mathematical, musical, visual-spatial, bodily-kinesthetic, interpersonal, and intrapersonal), later adding naturalistic and existential intelligences. One of these is linguistic (verbal-linguistic) intelligence, which is based on sensitivity to words, language, reading, writing, oral expression, and the rhythm, meaning, and sounds of language. Students with strong linguistic intelligence easily analyze texts, write stories, actively participate in debates, and effectively absorb information through language. An individualized teaching approach based on linguistic intelligence aims to adapt the learning process to each student’s linguistic strengths while supporting other intelligences, thereby improving the quality of education. This thesis examines the theoretical foundations of this approach, its practical application, research evidence on its effectiveness, and its limitations.